Exploring the Link Between Social Responsibility and Charitable Donations of Private Enterprises: Insights for Team Dynamics and Community Engagement in Sports - Shenan Hu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Over the past 30 years, private enterprises in China have emerged as key drivers of the nation’s economic development. However, challenges remain in effectively fulfilling their social responsibilities. Charitable donations serve as one of the most tangible indicators of social responsibility. Consequently, the relationship between private enterprises’ social responsibility and their financial performance has been a central topic in corporate management for over two decades. This study employs cosine similarity (CS) and minimum spanning tree (MST) methods to model the relationship between charitable donations, providing a framework to indirectly explore the connection between corporate social responsibility and charitable contributions in pursuit of the common prosperity goal. Experimental results demonstrate that this approach significantly outperforms traditional single-similarity modeling techniques, offering robust generalization capabilities. From a sports perspective, these findings provide insights into fostering community engagement and ethical practices among sports organizations. By emphasizing social responsibility through initiatives such as charitable donations, sports entities can enhance their societal impact, promote teamwork values, and contribute to the broader goal of common prosperity while building stronger ties with their communities.